SUSTAINABILITY OF AGROHOLDINGS IN EUROPE IN THE CONDITIONS OF DECENTRALIZATION OF THE ECONOMY - KHUDOLEI, Veronika (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the stability of agricultural holdings in Europe in the conditions of decentralization of the economy. It is established that the economic stability of agricultural holdings is a sphere of sustainable agriculture. Agricultural holdings must receive such income that they can cover all their expenses.The Common Agricultural Policy currently addresses many long-term issues, but it also has to deal with new challenges. It can simply be said that from a long-term perspective, the CAP (Common Agricultural Policy) in the EU aims to support farm incomes to achieve a balanced, productive agriculture. The relatively new focus of Green Europe is aimed at the mutual reciprocity of many different aspects with an emphasis on the environment. However, the economic stability of agricultural enterprises cannot be neglected in the picture of new policy goals. The study focuses on the issue of the double structure of farms, which is characterized by the different nature of two groups of agricultural enterprises and is found especially in countries that have undergone agricultural transformation. The dual structure of farms in agriculture is relatively unusual among EU states, for which a generally accepted EU methodology is insufficient.From the presented data, significant differences are noticeable both between the type of farm and between farms with different economic sizes within individual specializations. Farms of mixed production and milk production have the greatest load. Usually, large and very large farms employ paid workers, while small and medium-sized farms use their own labor. Larger holdings have more available external capital, which accounts for almost 40% of the total assets of livestock holdings. As the farm size increases, the share of land owned and the share of permanent pastures decreases.The largest share of sustainable farms was found in farms that focus on milk production. In terms of size, small farms are most at risk, which is confirmed for all production areas. On the contrary, larger and very large holdings were included in the group of viable holdings. This finding confirms the need to support the viability and sustainability of small extensive farms. These are farms focused on grazing livestock. These farms are located in remote areas that require sustainable maintenance. Agriculture is important to maintain employment and social interaction so that the countryside does not remain abandoned. An actual type of such support is redistribution. This methodology was applied as one of the impact assessment factors to determine it.
Keywords: sustainability; agricultural holdings; decentralization of the economy